A central role for ubiquitination within a circadian clock protein modification code - Stojkovic, Katarina; Wing, Simon S.; Cermakian, Nicolas (Frontiers in Molecular Neuroscience, 2014)
Circadian rhythms, endogenous cycles of about 24 h in physiology, are generated by a master clock located in the suprachiasmatic nucleus of the hypothalamus and other clocks located in the brain and peripheral tissues. Circadian disruption is known to increase the incidence of various illnesses, such as mental disorders, metabolic syndrome and cancer. At the molecular level, periodicity is established by a set of clock genes via autoregulatory translation-transcription feedback loops. This clock mechanism is regulated by post-translational modifications such as phosphorylation and ubiquitination, which set the pace of the clock. Ubiquitination in particular has been found to regulate the stability of core clock components, but also other clock protein functions. Mutation of genes encoding ubiquitin ligases can cause either elongation or shortening of the endogenous circadian period. Recent research has also started to uncover roles for deubiquitination in the molecular clockwork. Here we review the role of the ubiquitin pathway in regulating the circadian clock and we propose that ubiquitination is a key element in a clock protein modification code that orchestrates clock mechanisms and circadian behavior over the daily cycle.